Alternative formation of amides and β-enaminones from aroyl chlorides using the TiCl4-trialkylamine reagent system. Issue 31 (26th July 2018) - Leggio, Antonella; Comandè, Alessandra; Belsito, Emilia Lucia; Greco, Marianna; Lo Feudo, Lucia; Liguori, Angelo
Abstract : Synthesis of amides and β-enaminones by the reaction of aroyl chlorides with the TiCl4 –NR3 reagent system. Abstract : The TiCl4 /NR3 reagent system has been successfully employed for the synthesis of amides and β-enaminones. The reaction of variously substituted benzoyl chlorides with the TiCl4 /NR3 reagent system, by using two different experimental procedures (Method A and Method B), afforded alternatively the corresponding amides and β-enaminones as unique or major products. The two developed protocols were investigated with a series of tertiary amines. The reactions, modulated by the presence of TiCl4, provided the corresponding amides or β-enaminones with satisfactory yields. This paper reports a new method for carbon–carbon bond formation via the reaction of aroyl chlorides with the TiCl4 /NR3 reagent system.